Integrating Information into the Engineering Design Process - Fosmire, Michael; Radcliffe, David (Purdue University Press, 2013)
Engineering design is a fundamental problem-solving model used by the discipline. Effective problem-solving requires the ability to find and incorporate quality information sources. To teach courses in this area effectively, educators need to understand the information needs of engineers and engineering students and their information gathering habits. This book provides essential guidance for engineering faculty and librarians wishing to better integrate information competencies into their curricular offerings. The treatment of the subject matter is pragmatic, accessible, and engaging. Rather than focusing on specific resources or interfaces, the book adopts a process-driven approach that outlasts changing information technologies.After several chapters introducing the conceptual underpinnings of the book, a sequence of contributions go into detail about specific steps in the design process and the information needs for those steps.